IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE (AI) TECHNOLOGY IN GOOGLE SUITE-BASED LEARNING FOR ACCOUNTING TEACHERS AT VOCATIONAL HIGH SCHOOLS - Sumiati, Ati; Fauzi, Ahmad; Indriani, Susi; Kismayanti, Dwi; Azzahra, Freesta; Sejati, Maharani Amelia Putri; Afiati, Naila (International Journal of Engagement and Empowerment (IJE2), 2025)
The development of Artificial Intelligence (AI) technology has provided a great opportunity to revolutionize the world of education, especially in supporting more interactive, adaptive, and effective learning. However, at the school level, the understanding and utilization of Artificial Intelligence (AI) among educators or teachers remain very limited. Yet, technological literacy, including the use of Artificial Intelligence (AI), is an essential skill for addressing the challenges of education in the digital age. This community service program aims to enhance students' technological literacy through the implementation of Artificial Intelligence (AI) in Google Suite-based learning. This activity will provide training on the use of Artificial Intelligence (AI) features in Google Suite, such as Google Docs, Google Sheets, and Google Slides, which can be used to support the learning process. Educators or teachers will learn to optimize Artificial Intelligence (AI) technology to enhance productivity, creativity, and collaboration skills in various academic and professional contexts. The targeted outcomes include improving the skills of educators or teachers in using Artificial Intelligence (AI) for technology-based learning, the availability of digital training modules containing practical guidelines for integrating Artificial Intelligence (AI) into Google Suite, and the formation of a sustainable technology-based learning community that can serve as a model for other educational institutions.